KNOWLEDGE LEVEL OF LIVESTOCK FARMERS ON IMPROVED HUSBANDRY PRACTICES IN KASHMIR VALLEY (Indian Journal of Animal Production and Management, 2014)
The present study was carried out in hilly areas of district Budgam and Srinagar, Jammu and Kashmir during June, 2010 to May, 2013 to assess the level of knowledge among the livestock farmers and nature of disease prevalence in livestock. A total of 200 farmers were randomly selected from different awareness cum training programmes conducted and 500 numbers of clinical cases presented in Krishi Vigyan Kendra, Srinagar (Old Budgam) were considered for the study. The study revealed that 50.50, 61.50, 42.00 and 24.50% farmers were aware about the methods of concentrate feed preparation, silage / hay making, high yielding varieties fodder cultivation and utilization of medicated urea mineral block respectively. Similarly 68.50, 85.50, 34.50 and 39.50 % farmers were found to be aware about importance of Artificial Insemination (AI), heat detection, length and duration of estrus in cows and proper timing of AI in cows respectively. Regarding managemental practices 25.50, 69.50, 81.00, 76.00 and 65.50 % livestock holders were found to be aware about care of animals, cleaning /sanitation of animal shed, feeding of colostrum, manure disposal and castration of animals respectively. In respect of disease management, the farmers were more aware about vaccination of animals (75.50 %), vaccination of poultry (47.04 %), de-worming of animals (92.50 %), de-worming of poultry (19.50 %) and disposal of dead animals / birds (51.50 %). The highest numbers of clinical cases (72.00 %) recorded, were related to medicinal followed by reproductive disorders (24.80 %) and surgical cases (3.20 %).
Keywords: Knowledge; management; disease; livestock; Kashmir